2020
DOI: 10.1002/cne.25017
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical phenotype of growth hormone‐responsive cells in the mouse paraventricular nucleus of the hypothalamus

Abstract: Multiple neuroendocrine, autonomic and behavioral responses are regulated by the paraventricular nucleus of the hypothalamus (PVH). Previous studies have shown that PVH neurons express the growth hormone (GH) receptor (GHR), although the role of GH signaling on PVH neurons is still unknown. Given the great heterogeneity of cell types located in the PVH, we performed a detailed analysis of the neurochemical identity of GH‐responsive cells to understand the possible physiological importance of GH action on PVH n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 88 publications
(146 reference statements)
2
9
0
Order By: Relevance
“…Thus, acute changes in GHR signalling in dopaminergic neurones may be necessary to fully induce prolactin secretion during restraint stress. Of note, although our study focused on investigating ARH dopaminergic neurones as putative mediators of GH action to regulate prolactin secretion, different hypothalamic and brainstem areas contain TH‐expressing neurones that are responsive to GH, including the periventricular nucleus, paraventricular nucleus of the hypothalamus and locus coeruleus 19,42 . Additionally, we cannot rule out the participation of catecholaminergic cells of the periphery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, acute changes in GHR signalling in dopaminergic neurones may be necessary to fully induce prolactin secretion during restraint stress. Of note, although our study focused on investigating ARH dopaminergic neurones as putative mediators of GH action to regulate prolactin secretion, different hypothalamic and brainstem areas contain TH‐expressing neurones that are responsive to GH, including the periventricular nucleus, paraventricular nucleus of the hypothalamus and locus coeruleus 19,42 . Additionally, we cannot rule out the participation of catecholaminergic cells of the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone‐responsive neurones were identified in the present study via the expression of pSTAT5 in mice previously injected with GH. Although this method has been extensively used by our research group, 13,15‐19,29‐31,40‐43 we cannot guarantee that all pSTAT5 positive cells express GHR. Indeed, no study so far has demonstrated that TIDA neurones express Ghr mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of GHR signaling in several newly described populations of GH-responsive neurons remains undetermined [ 36 , 37 ]. Recently, our research group identified the neurochemical phenotype of GH-responsive cells in mouse PVH [ 104 ]. The PVH contains several neurochemically defined neuronal populations [ 105 ], so the identification of those that are responsive to GH allows understanding the possible physiological importance of GHR signaling in this hypothalamic nucleus.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The PVH contains several neurochemically defined neuronal populations [ 105 ], so the identification of those that are responsive to GH allows understanding the possible physiological importance of GHR signaling in this hypothalamic nucleus. We found that 38%, 55%, 35% and 63% of TH, SST, thyrotropin-releasing hormone (TRH) and corticotropin-releasing hormone (CRH) neurons exhibited GH-induced pSTAT5, respectively [ 104 ] ( Figure 3 B). The majority of neuroendocrine SST, TRH and CRH neurons were responsive to GH, indicating that central GH signaling probably regulates somatotropic, thyroid and adrenal endocrine axes ( Figure 2 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation